2007
DOI: 10.4236/jmmce.2007.61004
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Agitation Speed on the Morphology and Size Particle Synthesis of Zr(HPO<sub>4</sub>)<sub>2</sub>·H<sub>2</sub>O from Mexican Sand

Abstract: Mexican zirconium sand has been envisaged like a source of zirconium compounds. The main product obtained is zircon (ZrSiO 4), which has a high raw material value. During a mineralogical purification sand process with hydrofluoric acid, a liquor was obtained as the by product. This liquor was dripped over hot phosphoric acid to obtain zirconium hydrogen phosphate Zr(HPO 4) 2. H 2 O (α-ZP) which has taken considerably attention due to its wide application. Both products zircon and α-ZP were analyzed as for stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 14 publications
2
4
0
Order By: Relevance
“…The broad band around 750 cm –1 in the spectra of NbPO and ZrPO is attributed to the P–O–P vibration of diphosphate groups . The ZrPO band at 933 cm –1 was already observed in the α-zirconium hydrogen phosphate FTIR spectrum . The peak position of asymmetric P–O stretching vibrations usually increases in energy with the increasing ionic radius of the cation, which is in agreement with our experimental results [Nb (215 pm) < Zr (230 pm) < La (250 pm) → 981 cm –1 < 1013 cm –1 < 1072 cm –1 , respectively].…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The broad band around 750 cm –1 in the spectra of NbPO and ZrPO is attributed to the P–O–P vibration of diphosphate groups . The ZrPO band at 933 cm –1 was already observed in the α-zirconium hydrogen phosphate FTIR spectrum . The peak position of asymmetric P–O stretching vibrations usually increases in energy with the increasing ionic radius of the cation, which is in agreement with our experimental results [Nb (215 pm) < Zr (230 pm) < La (250 pm) → 981 cm –1 < 1013 cm –1 < 1072 cm –1 , respectively].…”
Section: Resultssupporting
confidence: 90%
“…In fact, the strong crystal field of LaPO splits the asymmetrical P–O stretching (ν 3 ) into four bands detectable at 1072, 1043, 1021, and 988 cm –1 and the deformation vibration (ν 4 ) into three peaks at 613, 580, and 536 cm –1 , respectively. Thanks to the high LaPO crystal field, even the symmetrical stretching vibration (ν 1 ) at 944 cm –1 was resolved, although it should be infrared-forbidden . The broad band around 750 cm –1 in the spectra of NbPO and ZrPO is attributed to the P–O–P vibration of diphosphate groups . The ZrPO band at 933 cm –1 was already observed in the α-zirconium hydrogen phosphate FTIR spectrum .…”
Section: Resultsmentioning
confidence: 99%
“…Thus, a higher rotation speed may lead to the change of nano-Ni’s morphology and increase in average particle size of nano-Ni. The similar phenomenon has been also found in the preparation of nano-Ni in the STR and the preparation of other particle in STR. , …”
Section: Resultssupporting
confidence: 80%
“…The similar phenomenon has been also found in the preparation of nano-Ni in the STR and the preparation of other particle in STR. 35,36 4.2. Effect of NaBH 4 Concentration.…”
Section: Methodsmentioning
confidence: 99%
“…In the last years, microstructural characterization of Zr alloys with titanium and other valve metals has been deeply investigated for their potential mechanical and biomedical applications [6,7]. Previous studies [8] have shown that anodizing Zr in H 3 PO 4 produces apart from ZrO 2 a superficial stratum rich in phosphates and other studies revealed [9] that the phosphates are usually formed as zirconium hydrogen phosphate (Zr(HPO 4 ) 2 .H 2 O), alpha phase (α-ZP) being the more common.…”
mentioning
confidence: 99%